2017
DOI: 10.1016/j.aju.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the risk factors associated with the development of post-transurethral resection of the prostate persistent bacteriuria

Abstract: ObjectivesTo determine the preoperative, intraoperative and postoperative risk factors that influence the development of persistent post-transurethral resection of the prostate (TURP) urinary tract infection (UTI) defined as pyuria and/or bacteriuria remaining for 3 weeks after surgery.Patients and methodsThis is a prospective study including 100 patients scheduled for TURP. Urine analysis and culture was performed immediately after catheter removal, then at 1 and 3 weeks postoperatively, and the results were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
5
6
1
3
Order By: Relevance
“…Pre-operative positive bacterial urine culture was identified as a risk factor for developing post-operative fever (8.5% vs. 1.2%, RR = 3.85 range 1.33-100, P < 0.05). DM, indwelling urethral catheter and TURP combined with cystolithotripsy were reported by Osman et al, [7] as independent risk factors for bacteriuria, but did not increase the risk for post-operative fever in our cohort. This was ostensibly due to the strict following of preoperative antibiotic coverage in our practice, preventing bacteriuria from becoming bacteremia.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Pre-operative positive bacterial urine culture was identified as a risk factor for developing post-operative fever (8.5% vs. 1.2%, RR = 3.85 range 1.33-100, P < 0.05). DM, indwelling urethral catheter and TURP combined with cystolithotripsy were reported by Osman et al, [7] as independent risk factors for bacteriuria, but did not increase the risk for post-operative fever in our cohort. This was ostensibly due to the strict following of preoperative antibiotic coverage in our practice, preventing bacteriuria from becoming bacteremia.…”
Section: Discussionsupporting
confidence: 69%
“…Due to our concern regarding record bias in accessing length of procedure, based on operation room registration in our cohort, we used prostate size as an indirect way of accessing operative time. Osman et al, reported prostate size larger > 60 cm 3 as a risk factor for UTI post-operatively [7]. In contrast, we found that smaller prostate size slightly increased the risk for post-operative fever with an RR of 1.06.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Japanese guide about prevention of perioperative infection [9] and ORENUC system by EAU/ESIU classify those risk factors as: patient associated factors and procedure associated factors [5, 10]. Among all of them, ASA physical status classification, immunosuppression, indwelling catheter and catheterization duration after surgery have been identified as risk factors in our study.…”
Section: Discussionmentioning
confidence: 96%